(untitled) - Chang, Raymond (Boston, Massachusetts, 1998)
The book provides a firm foundation in chemical concepts and principles, the three-dimensional atomic and molecular structures that are the basis of chemical activity. It also deals with the role chemistry plays in contemporary life and their curiosity about the "central science"
Keywords: Chemistry